Efeito de agentes clareadores à base de peróxido de hidrogênio sobre a fluorescência de resinas compostas - Bueno, Renata Plá Rizzolo (2010)
Due to the increasing search for an aesthetic smile, the demand for less invasive procedures, such as in composite restoration and tooth bleaching, also increased. The composite resins have optical properties and one of these properties is the fluorescence which is intended to give naturalness to restoration mimicking them in the natural dentition. The aim of this study was to evaluate the effect of bleaching agents based on hydrogen peroxide on the fluorescence of different composites. For this, 30 specimens were made, 10 for each composite resin (4 Seasons and Opallis), measuring 10mm in diameter and 2mm thickness with the aid of a matrix of acrylic split. After fabrication, the samples were polished on politriz with abrasive paper grit 600, 1.200 and 2.500. Before exposing the specimens to the bleaching agents (White Class 7.5% with calcium and Whiteness HP Blue 35% with calcium) was held the first reading of fluorescence through the apparatus fluorescence spectrophotometer Cary Eclipse. Exposures to hydrogen peroxide were performed according to the manufacturers. After this procedure (30 days) was performed the second reading of fluorescence. The values were statistically analyzed by paired t test, Student t test, analyses of variance and multiples comparisons test of Tukey (p <0.05). The results showed that the composite resins evaluated had different behaviors in all groups, and after exposure to hydrogen peroxide 7.5% only 4 Seasons significantly changed and the Opallis significantly changed when stored in deionized water. The resin Opallis showed more instability in relation to the fluorescence, hydrogen peroxide 7.5% (homemade method) determined the biggest changes in the values of fluorescence and time of exposure to the bleaching agent affected more the fluorescence of the resin composite 4 Seasons than its concentration.